DEEPFAKE ART THREAT OR INNOVATION IN DIGITAL CREATIVITY - Pandey, Arvind Kumar; Minhas, Deepak; Eeshita Goyal, Eeshita; Bhowmik, Mahua; Khajanchi, Yukti; Dhawan, Aashim (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The boundaries of the digital creativity have been re-established with the introduction of the deepfake technology, which is facilitated by advanced artificial intelligence and machine learning algorithms. Deepfake art is an act of creating and altering images and audio to generate hyper-realistic and artificial images. It is also highly ethical, legal, and social because it has massive potential in the field of innovation in the sphere of film production, advertising, education, and digital art. The Deepfake technology as an art tool gives artists an opportunity to experiment with the identity, transformation, and imagination in a manner never witnessed previously, and challenges the traditional concepts of authenticity and originality. However, it represents enormous threats to privacy, trust and integrity of information due to its abuse as an instrument of misinformation, non-consent information and political propaganda. With the assistance of the multidisciplinary approach that involves the ethics, law, media studies, and art theory, it is only possible to understand its implications. This paper explains why deepfake art can be both a new paradigm and a menace simultaneously and why regulation systems, digital literacy, and responsible art are needed to ensure that social protection is not subordinated to freedom of artistic expression.